Environment-friendly total-synthesis water-based aluminum alloy cutting fluid and preparation method thereof
By adding specific chemical components and nanofluids to the cutting fluid and performing microwave-ultrasound treatment, the problem of insufficient lubrication and cooling performance of the existing cutting fluid is solved, and the improvement of efficient lubrication, good cooling and environmental protection performance is achieved.
Patent Information
- Application Number
- CN202411747015.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The lubricating and cooling properties of existing cutting fluids are poor, and contain harmful substances, which affects environmental protection performance.
The environmentally friendly fully synthesized aqueous aluminum alloy cutting fluid is used to design chemical components reasonably, and the addition of diethylene glycol dimethyl ether, sulfolane, dolomite/zirconia-based nanofluids and other components are added to improve lubricity and cooling performance, and the stability and cleaning performance are improved through microwave-ultrasound combined treatment.
It significantly improves the lubrication and cooling performance of cutting fluid, extends the tool service life, reduces environmental pollution, and achieves the improvement of environmental protection performance.
Smart Images

Figure CN119570551A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cutting fluids, and in particular to an environmentally friendly fully synthetic water-based aluminum alloy cutting fluid and a preparation method thereof. Background Art
[0002] Cutting fluid is an industrial liquid used in metal cutting and grinding processes to cool and lubricate tools and workpieces. It provides necessary cooling, lubrication and rust protection for tools and workpieces by spraying or immersing during the processing, thereby improving processing efficiency, ensuring processing quality and extending tool life. Cutting fluid is scientifically compounded with a variety of super-functional additives, and has good cooling performance, lubrication performance, rust prevention performance, oil removal and cleaning function, anti-corrosion function, and easy dilution.
[0003] However, changes in cutting conditions (such as speed and thickness) affect the formation and stability of the lubricating film, resulting in poor lubrication performance of the cutting fluid; the existing cutting fluid has a low thermal conductivity and cannot effectively transfer heat, resulting in poor cooling performance of the cutting fluid; the cutting fluid contains harmful substances such as chlorine, sulfur, phenol, nitrite, etc., which are not easily biodegradable and may cause long-term pollution when discharged into the environment, and the waste generated during the use of the cutting fluid is not properly handled, causing pollution to the environment. Therefore, how to simultaneously improve the lubrication performance, cooling performance and environmental protection performance of the cutting fluid is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides an environmentally friendly fully synthetic water-based aluminum alloy cutting fluid and a preparation method thereof to solve the following technical problem: how to simultaneously improve the lubrication performance, cooling performance and environmental performance of the cutting fluid.
[0005] In a first aspect, the present application provides an environmentally friendly fully synthetic water-based aluminum alloy cutting fluid, which is composed of the following chemical components, measured by mass: diethylene glycol dimethyl ether: 2.0 to 5.0 parts, triethanolamine: 0.5 to 1.5 parts, sodium chloride: 0.1 to 1.0 parts, sulfolane: 1.0 to 3.0 parts, surfactant: 0.5 to 1.5 parts, aluminum corrosion inhibitor: 0.1 to 1.0 parts, extreme pressure agent: 0.05 to 0.3 parts, dolomite / zirconia-based nanofluid: 85 to 96 parts;
[0006] Wherein, the dolomite / zirconia-based nanofluid consists of dolomite, zirconium oxide, quaternized sodium alginate and deionized water.
[0007] Optionally, the dolomite is 0.3-0.7% of the total mass of the dolomite / zirconia-based nanofluid; and / or,
[0008] The zirconium oxide is 0.1-0.3% of the total mass of the dolomite / zirconia-based nanofluid; and / or,
[0009] The mass of the quaternized sodium alginate is 0.05-0.15% of the total mass of the dolomite / zirconia-based nanofluid.
[0010] Optionally, the aluminum corrosion inhibitor consists of a siloxane ketone corrosion inhibitor and a phosphate ester corrosion inhibitor, and the mass ratio of the siloxane ketone corrosion inhibitor to the phosphate ester corrosion inhibitor is (1-3):1.
[0011] Optionally, the extreme pressure agent is composed of dialkyl dithiocarbamate molybdenum and sodium metaborate, and the mass ratio of the dialkyl dithiocarbamate molybdenum to the sodium metaborate is (0.5-1.5):1.
[0012] Optionally, the surfactant is composed of an oleic acid amide-based nonionic surfactant and an alkyl imidazoline borate, and the ratio of the oleic acid amide-based nonionic surfactant to the alkyl imidazoline borate is (3-8):1.
[0013] Optionally, the particle size of the dolomite is 20 to 50 nm; and / or,
[0014] The particle size of the zirconium oxide is 1 to 10 nm.
[0015] In a second aspect, the present application provides a method for preparing the cutting fluid according to any one embodiment of the first aspect, the method comprising:
[0016] A dolomite / zirconia-based nanofluid is obtained;
[0017] Under stirring, adding diethylene glycol dimethyl ether, triethanolamine, sodium chloride, sulfolane, a surfactant, an aluminum corrosion inhibitor and an extreme pressure agent to the dolomite / zirconia-based nanofluid in sequence to obtain a mixed solution;
[0018] The mixed liquid is subjected to microwave-ultrasound combined treatment to obtain the cutting fluid.
[0019] Optionally, the process parameters of the microwave-ultrasonic combined treatment include: microwave power of 50 to 150 W, ultrasonic power of 100 to 200 W, and combined treatment time of 60 to 180 s.
[0020] Optionally, the preparation method of the dolomite / zirconia-based nanofluid comprises:
[0021] ball-milling dolomite and zirconium oxide to obtain a mixture;
[0022] The mixture, quaternized sodium alginate and deionized water are mixed, and then subjected to homogenization and dispersion treatment to obtain the dolomite / zirconia-based nanofluid.
[0023] Optionally, the homogenization and dispersion process includes the following parameters: a homogenization pressure of 100 to 140 MPa, and a homogenization time of 10 to 30 min.
[0024] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0025] The present application provides an environmentally friendly fully synthetic water-based aluminum alloy cutting fluid, which rationally designs the chemical components of the cutting fluid, improves lubricity and reduces cutting force and cutting temperature by adding diethylene glycol dimethyl ether (DEDM); improves the alkali reserve and pH stability of the cutting fluid by adding triethanolamine; changes the ionic strength and conductivity of the cutting fluid by adding sodium chloride, and enhances stability and hard water resistance; improves the polarity and solubility of the cutting fluid by adding sulfolane, and enhances lubrication and cooling performance; improves lubrication and cooling effects by adding dolomite / zirconia-based nanofluids, with dolomite and zirconium oxide as nanoparticles, and enhances rust prevention, stability and cleaning performance by quaternized sodium alginate. At the same time, the various components of the cutting fluid of the present application have significant synergistic effects. DEDM, triethanolamine, cyclopentane sulfone and dolomite and zirconium oxide in the nanofluid act together on the cutting interface to form a more effective lubricating film, significantly reducing the friction coefficient and cutting force; the high boiling point and high thermal stability of cyclopentane sulfone combined with the high purity of deionized water can more effectively absorb and take away the cutting heat, and reduce the temperature of the tool and the workpiece; the aluminum corrosion inhibitor, triethanolamine and quaternized sodium alginate work together to form a denser protective film to prevent metal corrosion; the surfactant, cyclopentane sulfone and the permeability of nanoparticles are combined to more effectively remove the debris and oil generated by cutting; sodium chloride, triethanolamine, quaternized sodium alginate in the nanofluid and other additives work together to improve the stability of the cutting fluid and prevent stratification, precipitation and deterioration; nano-scale zirconium oxide and dolomite particles affect the generation and stability of foam by providing a stable solid interface; at the same time, quaternized sodium alginate as a surfactant or dispersant can also adjust the stability of the foam, thereby synergistically improving the defoaming performance of the cutting fluid. In addition, the cutting fluid of the present application does not contain harmful substances, such as chlorine, sulfur, nitrite, etc., and is easily biodegradable, thereby improving the lubrication performance, cooling performance and environmental protection performance of the cutting fluid at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0028] Figure 1 A schematic flow chart of a method for preparing a cutting fluid provided in an embodiment of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0031] The present application provides an environmentally friendly fully synthetic water-based aluminum alloy cutting fluid, which is composed of the following chemical components by mass: 2.0 to 5.0 parts of diethylene glycol dimethyl ether, 0.5 to 1.5 parts of triethanolamine, 0.1 to 1.0 parts of sodium chloride, 1.0 to 3.0 parts of sulfolane, 0.5 to 1.5 parts of surfactant, 0.1 to 1.0 parts of aluminum corrosion inhibitor, 0.05 to 0.3 parts of extreme pressure agent, and 85 to 96 parts of dolomite / zirconia-based nanofluid;
[0032] Wherein, the dolomite / zirconia-based nanofluid consists of dolomite, zirconium oxide, quaternized sodium alginate and deionized water.
[0033] In some embodiments, the dolomite is 0.3-0.7% of the total mass of the dolomite / zirconia-based nanofluid; and / or,
[0034] The zirconium oxide is 0.1-0.3% of the total mass of the dolomite / zirconia-based nanofluid; and / or,
[0035] The mass of the quaternized sodium alginate is 0.05-0.15% of the total mass of the dolomite / zirconia-based nanofluid.
[0036] This application rationally designs the chemical components of the cutting fluid, and each component plays an important role, as follows:
[0037] Diethylene glycol dimethyl ether (DEDM): (1) Improve lubricity. As a component of cutting fluid, DEDM can increase the lubricity of cutting fluid, thereby reducing cutting force and cutting temperature, improving processing efficiency and workpiece quality. The improvement of its lubricity helps reduce tool wear and extend tool life. (2) Reduce friction coefficient. DEDM can reduce the surface tension of cutting fluid and reduce the contact angle between the cutting fluid on the workpiece surface and the tool, thereby reducing the friction coefficient. This effect of reducing the friction coefficient helps to reduce energy loss during the cutting process and improve cutting efficiency. (3) Anti-rust effect. DEDM also has certain anti-rust properties. It can absorb moisture in the air and form a protective film to effectively prevent metal oxidation and rust during the cutting process. This anti-rust effect helps protect the cutting parts from corrosion damage and improve the surface quality and service life of the cutting parts. (4) Improve the stability of cutting fluid. The addition of DEDM can also improve the stability of cutting fluid. It can prevent the cutting fluid from stratification and precipitation during use, thereby extending the service life of the cutting fluid. Stable cutting fluid helps to maintain the continuous stability of cutting performance, improve machining accuracy and production efficiency. DEDM is a relatively environmentally friendly compound with good biodegradability and little impact on the environment.
[0038] Triethanolamine: (1) Improve the alkali reserve and pH stability of the cutting fluid. (2) Enhance the anti-rust performance of the cutting fluid. (3) Improve the emulsification performance of the cutting fluid. Triethanolamine has a strong emulsification effect. It can fully mix the oily components and aqueous components in the cutting fluid to form a uniform emulsion. (4) Improve the lubrication performance of the cutting fluid. Triethanolamine also has certain lubrication properties. It can form a lubricating film during the cutting process to reduce the friction and wear between the workpiece and the tool.
[0039] Sodium chloride: Sodium chloride can undergo ion exchange or complex reaction with quaternized sodium alginate, thereby changing the ionic strength and conductivity of the cutting fluid. This helps to enhance the stability and hard water resistance of the cutting fluid and prevent the cutting fluid from deteriorating or precipitating under hard water conditions.
[0040] Sulfolane: (1) Improve the polarity and solubility of cutting fluid. Sulfolane is a highly polar solvent with good solubility for a variety of organic substances and polymers. In cutting fluid, sulfolane can increase the polarity of cutting fluid, thereby improving its solubility for oily components and other additives. This helps the cutting fluid remain uniform and stable during use, avoiding stratification and precipitation. (2) Enhance the lubrication performance of cutting fluid. The polarity of sulfolane enables it to form a good lubricating film with the metal surface, reducing friction and wear during cutting. At the same time, sulfolane also has a certain diffusion effect, which can quickly penetrate into the cutting area and provide continuous lubrication. This helps to extend the service life of the tool, improve processing efficiency and workpiece quality. (3) Improve the cooling performance of cutting fluid. A large amount of heat is generated during the cutting process, and the cutting fluid needs to have good cooling performance to remove the heat in time to prevent overheating of the workpiece and tool. The high boiling point and high thermal stability of sulfolane enable it to maintain stable performance at high temperatures, thereby effectively reducing the cutting temperature and protecting the workpiece and tool from thermal damage. (4) Improve the cleaning performance of cutting fluid. The cutting fluid also needs to have good cleaning properties during the cutting process to remove the debris and impurities generated by cutting. The solubility and fluidity of sulfolane help the cutting fluid to better penetrate into the cutting area, remove the debris and impurities, and keep the cutting area clean.
[0041] Surfactants: reduce the surface tension of liquids.
[0042] Aluminum corrosion inhibitor: protect aluminum alloy materials from corrosion during cutting. Inhibit corrosion: Aluminum corrosion inhibitor can effectively inhibit the corrosion reaction of aluminum alloy in cutting fluid, and prevent discoloration, corrosion and other problems on the surface of aluminum alloy. Protect cutting parts: By adding aluminum corrosion inhibitor, cutting parts can be protected from corrosion damage during cutting, and the surface quality and service life of cutting parts can be improved.
[0043] Extreme pressure agent: Improves the extreme pressure performance of the cutting fluid, thereby providing better lubrication and cooling effects during the cutting process.
[0044] Dolomite / zirconia-based nanofluids: Dolomite is a layered silicate mineral that can be used as a solid lubricant to form a lubricating film during the cutting process through its layered structure. Zirconia nanoparticles can be used as abrasives to help remove metal chips generated during the cutting process, while improving the lubrication and cooling properties of the cutting fluid. Quaternized sodium alginate has excellent water solubility, stability and adhesion. It can better infiltrate and adsorb on the surface of dolomite / zirconia through interactions such as hydrogen bonds and interactions between hydrophobic sites. The high viscosity can better transmit shear force to ensure the stable dispersion of dolomite / zirconia and prevent the agglomeration of dolomite / zirconia. Specifically, it has the following effects: (1) Improve the lubrication properties of the cutting fluid. Dolomite and zirconia are added to the cutting fluid as nanoparticles. Due to their extremely small particle size and high specific surface area, they can more effectively form a lubricating film at the cutting interface. This lubricating film can significantly reduce the friction coefficient between the tool and the workpiece, thereby reducing cutting force and cutting temperature, reducing tool wear, and improving processing efficiency and processed surface quality. (2) Enhance the cooling effect of the cutting fluid. As a component of nanofluids, deionized water has high purity and good thermal conductivity. It can more effectively absorb and take away the heat generated during the cutting process, thereby reducing the temperature of the tool and workpiece and extending their service life. At the same time, the addition of nanoparticles can also increase the thermal conductivity of the cutting fluid and further improve the cooling effect. (3) Improve the anti-rust performance of the cutting fluid. Quaternized sodium alginate is an effective rust inhibitor that can form a protective film on the metal surface to prevent the metal from corroding due to contact with corrosive substances in the cutting fluid. In addition, the addition of nanoparticles can also work synergistically with the rust inhibitor to form a denser protective film, further enhancing the anti-rust performance of the workpiece. (4) Improve the cleaning performance of the cutting fluid. The addition of nanoparticles can increase the permeability and cleaning ability of the cutting fluid. They can penetrate into the tiny gaps in the cutting area, remove impurities such as debris and oil generated by cutting, and keep the cutting area clean. At the same time, the use of deionized water can also reduce the electrolyte content in the cutting fluid and reduce the risk of electrochemical corrosion. (5) Improve the stability of the cutting fluid. The nanoparticles in nanofluids have a small particle size and are evenly distributed, which helps the cutting fluid maintain stability during use. They can prevent the cutting fluid from stratification and precipitation, thereby extending the service life of the cutting fluid. In addition, the addition of additives such as quaternized sodium alginate can also improve the antibacterial properties of the cutting fluid and prevent the cutting fluid from deteriorating and stinking during use. (6) Improve defoaming properties: Nano-scale zirconium oxide and dolomite particles can affect the generation and stability of foam by providing a stable solid interface; at the same time, quaternized sodium alginate as a surfactant or dispersant can also improve the stability of the foam.
[0045] In some embodiments, the aluminum corrosion inhibitor is composed of a siloxane ketone corrosion inhibitor and a phosphate ester corrosion inhibitor, and the mass ratio of the siloxane ketone corrosion inhibitor to the phosphate ester corrosion inhibitor is (1-3):1.
[0046] Siloxanone corrosion inhibitors and phosphate corrosion inhibitors are complementary in molecular structure. Siloxanone corrosion inhibitors mainly provide physical adsorption and hydrophobic barriers, while phosphate corrosion inhibitors form dense chemical films through chemical conversion. The two work together to form a multi-layer, multifunctional corrosion inhibition system. At the same time, there are intermolecular interactions (such as hydrogen bonds, van der Waals forces, etc.) between the corrosion inhibition film formed by siloxanone corrosion inhibitors and the chemical conversion film formed by phosphate corrosion inhibitors, which enables the two films to be tightly combined to form a more stable and dense protective layer. In addition, due to the synergistic effect of siloxanone corrosion inhibitors and phosphate corrosion inhibitors, the protective layer formed not only has excellent water resistance and oxidation resistance, but also can effectively resist the erosion of corrosive ions such as chloride ions and sulfate ions. This allows the aluminum corrosion inhibitor in the cutting fluid to maintain excellent anti-rust performance in harsh cutting environments.
[0047] In some embodiments, the extreme pressure agent is composed of molybdenum dialkyl dithiocarbamate and sodium metaborate, and the mass ratio of the molybdenum dialkyl dithiocarbamate to the sodium metaborate is (0.5-1.5):1.
[0048] When MoDTC and sodium metaborate exist at the same time, they will interact to a certain extent and form a more uniform, dense and strong protective film on the metal surface. This synergistic film-forming effect can further improve the extreme pressure performance and lubrication performance of the cutting fluid. The molecular structure of MoDTC contains thiocarbamate (DTC), which enables it to form a lubricating film with extreme pressure and anti-wear properties on the metal surface. The molecular structure of sodium metaborate is relatively simple, but the boron atoms and oxygen atoms it contains can react chemically with the metal surface to form a protective film. Although this protective film may not be as complex as the film formed by MoDTC, it can increase the lubricity and stability of the cutting fluid. When the two are mixed in an appropriate proportion, their molecular structures can complement each other and form a more complete protective film on the metal surface. This protective film can not only prevent direct contact and wear between metals, but also reduce friction and cutting heat during cutting, thereby improving cutting efficiency and processing quality.
[0049] In some embodiments, the surfactant is composed of an oleic acid amide-based nonionic surfactant and an alkyl imidazoline borate, and the ratio of the oleic acid amide-based nonionic surfactant to the alkyl imidazoline borate is (3-8):1.
[0050] When OMA and alkyl imidazoline borate are mixed in an appropriate proportion, their molecular structures can complement each other. The long carbon chain hydrocarbon group of OMA and the non-polar group of alkyl imidazoline borate jointly provide hydrophobicity and lubricity, while the polar group of OMA and the polar group of alkyl imidazoline borate jointly provide wetting, emulsification and rust prevention functions. This complementarity of molecular structure enables the cutting fluid to form a more complete and stable protective film during metal processing, thereby improving its extreme pressure performance, lubrication performance and rust prevention performance. OMA and alkyl imidazoline borate molecules can adsorb and arrange each other in the cutting fluid to form a more uniform and dense protective film. This synergistic film-forming effect can further improve the lubrication and rust prevention performance of the cutting fluid. The synergistic effect of OMA and alkyl imidazoline borate can also improve the stability of the cutting fluid. They can mutually restrict and balance the various components in the cutting fluid to prevent them from decomposing, deteriorating or precipitating during use.
[0051] In some embodiments, the dolomite has a particle size of 20 to 50 nm; and / or,
[0052] The particle size of the zirconium oxide is 1 to 10 nm.
[0053] The particle size of dolomite is limited to 20-50 nm, and the particle size of zirconium oxide is limited to 1-10 nm, so as to facilitate the dispersibility and stability of dolomite and zirconium oxide in the nanofluid.
[0054] Figure 1 A schematic flow chart of a method for preparing a cutting fluid provided in an embodiment of the present application.
[0055] Based on a general inventive concept, the present application provides a method for preparing a cutting fluid as described in any one of the above embodiments, the method comprising:
[0056] S1, obtaining dolomite / zirconia-based nanofluid;
[0057] In some embodiments, the method for preparing the dolomite / zirconia-based nanofluid comprises:
[0058] ball-milling dolomite and zirconium oxide to obtain a mixture;
[0059] The mixture, quaternized sodium alginate and deionized water are mixed, and then subjected to homogenization and dispersion treatment to obtain the dolomite / zirconia-based nanofluid.
[0060] In some embodiments, the homogenization and dispersion process includes the following parameters: a homogenization pressure of 100 to 140 MPa, and a homogenization time of 10 to 30 min.
[0061] Homogenization uses a high-pressure homogenizer to apply high pressure and shear force to the material through a special homogenization valve or impact head. The specific effects of homogenization are as follows: (1) Improving dispersion uniformity: Homogenization can destroy the agglomeration and aggregation between material particles, dispersing them into smaller, uniform particles. In the preparation of dolomite / zirconia-based nanofluids, homogenization can ensure that dolomite and zirconia particles are evenly distributed in the fluid to avoid local concentrations that are too high or too low. (2) Reducing particle size: Through homogenization, the size of material particles can be further refined to the nanometer level. Nano-scale particles have a larger specific surface area and higher reactivity, which is conducive to better lubrication and cooling in cutting fluids. (3) Enhancing stability: Homogenization can improve the interaction between material particles and fluids and enhance the stability of the system. In the preparation of dolomite / zirconia-based nanofluids, homogenization can prevent particle agglomeration and sedimentation and extend the service life of the cutting fluid. (4) Improve cutting fluid performance: The homogenized dolomite / zirconia-based nanofluid has higher lubricity, heat absorption and environmental protection properties. These performance improvements help reduce friction and wear during the cutting process, improve processing efficiency and workpiece quality.
[0062] S2. Under stirring, adding diethylene glycol dimethyl ether, triethanolamine, sodium chloride, sulfolane, a surfactant, an aluminum corrosion inhibitor and an extreme pressure agent to the dolomite / zirconia-based nanofluid in sequence to obtain a mixed solution;
[0063] S3, subjecting the mixed liquid to microwave-ultrasound combined treatment to obtain the cutting fluid.
[0064] In some embodiments, the process parameters of the microwave-ultrasound combined treatment include: microwave power of 50 to 150 W, ultrasonic power of 100 to 200 W, and combined treatment time of 60 to 180 s.
[0065] Nanofluid is used as cutting agent. The inorganic particles (such as dolomite or zirconium oxide) in the nanofluid can provide additional lubrication effect and reduce friction and wear during cutting due to its small size and special physical and chemical properties. However, nanofluid is not good at improving other properties of cutting fluid (such as cooling, rust resistance, cleaning, etc.), which limits the wide application of nanofluid in cutting fluid. The present application adds additives such as diethylene glycol dimethyl ether, triethanolamine, sodium chloride, cyclopentane, surfactant, aluminum corrosion inhibitor and extreme pressure agent to the nanofluid to improve the remaining properties of the cutting fluid. However, the presence of nanoparticles changes the physical and chemical properties of the fluid, thereby affecting the solubility and dispersibility of the additive. Therefore, the present application creatively carries out microwave-ultrasound treatment on the cutting fluid, which can promote the movement and dispersion of the additive molecules, thereby improving its solubility and dispersibility in the nanofluid. At the same time, microwave and ultrasound each have a unique mechanism of action in the cutting fluid treatment process, and their combined use can produce a synergistic effect. Microwaves mainly use high-frequency electromagnetic waves to make the molecules in the cutting fluid vibrate and rub rapidly, thereby generating heat to achieve the purpose of heating and extraction. Ultrasound, on the other hand, uses high-frequency sound waves to produce cavitation effects, microjets and shock waves, etc., to peel off, disperse and crush impurities and particles in the cutting fluid. The combination of these two effects can more effectively improve the cleanliness and performance of the cutting fluid. In addition, under the specified process parameters of microwave-ultrasound combined treatment, the components of the cutting fluid will not decompose.
[0066] Therefore, by subjecting the cutting fluid to microwave-ultrasonic treatment, the performance of the cutting fluid can be positively affected in many aspects. Specifically, as follows: (1) Improving the cooling and lubricating properties of the emulsion. Microwave-ultrasonic treatment can reduce the particle size of the emulsion molecules, making it easier for them to penetrate into the capillaries in the cutting area. This change in the microstructure helps to improve the cooling and lubricating properties of the cutting fluid, thereby more effectively reducing the temperature, friction and wear during the cutting process. (2) Enhancing the stability of the cutting fluid. Through microwave-ultrasonic treatment, the components in the cutting fluid can be more evenly dispersed and dissolved, reducing the occurrence of stratification and precipitation. This helps to improve the stability of the cutting fluid, extend its service life, and reduce the reduction in cutting performance caused by the deterioration of the cutting fluid. (3) Improving the cleaning performance of the cutting fluid. The energy generated by microwave-ultrasonic treatment can destroy the structure of dirt and impurities in the cutting fluid, making it easier to clean. This helps to keep the cutting area clean, reduce friction and resistance during the cutting process, and improve cutting efficiency and processing quality. (4) Improving the anti-rust performance of the cutting fluid. Aluminum corrosion inhibitors are important components in cutting fluids, used to prevent corrosion of metals such as aluminum alloys during the cutting process. Microwave-ultrasonic treatment can help to evenly distribute and adsorb aluminum corrosion inhibitors in cutting fluids, thereby enhancing their anti-rust properties and protecting cutting parts from corrosion damage. (5) Optimize the extreme pressure properties of cutting fluids. Extreme pressure agents play a role in providing additional lubrication and extreme pressure properties under high temperature and high pressure in cutting fluids. Microwave-ultrasonic treatment can help to disperse and activate extreme pressure agents in cutting fluids, thereby improving their extreme pressure properties and ensuring the smooth progress of the cutting process under extreme conditions. (6) Promote the environmental performance of cutting fluids. Microwave-ultrasonic treatment is a physical treatment method that does not require the addition of additional chemical reagents. Therefore, it helps to reduce environmental pollution during the preparation and use of cutting fluids, which is in line with the current trend of green manufacturing and sustainable development.
[0067] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0068] Example 1
[0069] The present embodiment provides an environmentally friendly fully synthetic water-based aluminum alloy cutting fluid, which is composed of the following chemical components by mass fraction: 3 parts of diethylene glycol dimethyl ether, 1 part of triethanolamine, 0.5 parts of sodium chloride, 2 parts of sulfolane, 1 part of surfactant, 0.5 parts of aluminum corrosion inhibitor, 0.15 parts of extreme pressure agent, and 91.85 parts of dolomite / zirconia-based nanofluid;
[0070] Wherein, the dolomite / zirconia-based nanofluid is composed of dolomite (CAS No.: 69227-00-5), zirconium oxide, quaternized sodium alginate and deionized water, wherein the dolomite is 0.5% of the total mass of the dolomite / zirconia-based nanofluid, the zirconium oxide is 0.2% of the total mass of the dolomite / zirconia-based nanofluid, and the mass of the quaternized sodium alginate is 0.1% of the total mass of the dolomite / zirconia-based nanofluid. The particle size of the dolomite is 40nm, and the particle size of the zirconium oxide is 5nm. The preparation method of the quaternized sodium alginate comprises: dissolving sodium alginate (Shanghai Aladdin Biochemical Technology Co., Ltd., viscosity of 200±20mPa·s) in deionized water and stirring until completely dissolved, adding 2,3-epoxypropyltrimethylammonium chloride and stirring thoroughly, and placing the reaction in a 60°C agitator away from light for 24 hours. Adjust the pH value to below 7 and then place it at room temperature. Excess ethanol is added for precipitation, and the product is collected and dried to obtain quaternized sodium alginate.
[0071] The aluminum corrosion inhibitor consists of a siloxane ketone corrosion inhibitor (MILLION siloxane ketone aluminum corrosion inhibitor AC-3S) and a phosphate ester corrosion inhibitor (Xipeng DX512 phosphate ester corrosion inhibitor), and the mass ratio of the siloxane ketone corrosion inhibitor to the phosphate ester corrosion inhibitor is 2:1.
[0072] The extreme pressure agent is composed of molybdenum dialkyl dithiocarbamate (CAS: 71342-89-7) and sodium metaborate (CAS: 10555-76-7), and the mass ratio of the molybdenum dialkyl dithiocarbamate to the sodium metaborate is 1:1.
[0073] The surfactant is composed of an oleic acid amide-based nonionic surfactant (Kemed oleic acid amide, CAS No.: 5301-02-0) and an alkyl imidazoline borate (alkyl imidazoline borate MB-1), and the ratio of the oleic acid amide-based nonionic surfactant to the alkyl imidazoline borate is 5:1.
[0074] Based on the above-mentioned environmentally friendly fully synthetic water-based aluminum alloy cutting fluid, this embodiment also provides a preparation method thereof, comprising the following steps:
[0075] S11, ball milling dolomite, zirconium oxide and a small amount of deionized water, the ball milling beads are made of agate, the ball-to-material ratio is 3:1, and the ball milling speed is 700r / min to obtain a mixture; the mixture, quaternized sodium alginate and deionized water are mixed, and then a high-pressure homogenizer is used for homogenization and dispersion to obtain the dolomite / zirconia-based nanofluid; the homogenization and dispersion treatment includes the following parameters: the homogenization pressure is 120MPa, and the homogenization time is 20min;
[0076] S21, under stirring, sequentially adding diethylene glycol dimethyl ether, triethanolamine, sodium chloride, sulfolane, a surfactant, an aluminum corrosion inhibitor and an extreme pressure agent to the dolomite / zirconia-based nanofluid to obtain a mixed solution;
[0077] S31, using a microwave ultrasonic synthesis extractor to perform microwave-ultrasonic combined treatment on the mixed liquid to obtain the cutting fluid. The process parameters of the microwave-ultrasonic combined treatment include: microwave power of 100W, ultrasonic power of 150W, and combined treatment time of 120s.
[0078] Example 2
[0079] This embodiment is modified as follows based on the disclosure of Embodiment 1:
[0080] The cutting fluid is composed of the following chemical components by mass fraction: 2.0 parts of diethylene glycol dimethyl ether, 0.5 parts of triethanolamine, 0.1 parts of sodium chloride, 1.0 parts of sulfolane, 0.5 parts of surfactant, 0.1 parts of aluminum corrosion inhibitor, 0.05 parts of extreme pressure agent, and 95.75 parts of dolomite / zirconia-based nanofluid.
[0081] Example 3
[0082] This embodiment is modified as follows based on the disclosure of Embodiment 1:
[0083] The cutting fluid is composed of the following chemical components by mass fraction: 5.0 parts of diethylene glycol dimethyl ether, 1.5 parts of triethanolamine, 1.0 parts of sodium chloride, 3.0 parts of sulfolane, 1.5 parts of surfactant, 1.0 parts of aluminum corrosion inhibitor, 0.3 parts of extreme pressure agent, and 86.7 parts of dolomite / zirconia-based nanofluid.
[0084] Example 4
[0085] This embodiment is modified as follows based on the disclosure of Embodiment 1:
[0086] The dolomite content is 0.3% of the total mass of the dolomite / zirconia-based nanofluid, the zirconium oxide content is 0.1% of the total mass of the dolomite / zirconia-based nanofluid, and the mass of the quaternized sodium alginate content is 0.05% of the total mass of the dolomite / zirconia-based nanofluid.
[0087] Example 5
[0088] This embodiment is modified as follows based on the disclosure of Embodiment 1:
[0089] The dolomite accounts for 0.7% of the total mass of the dolomite / zirconia-based nanofluid, the zirconium oxide accounts for 0.3% of the total mass of the dolomite / zirconia-based nanofluid, and the mass of the quaternized sodium alginate accounts for 0.15% of the total mass of the dolomite / zirconia-based nanofluid.
[0090] Comparative Example 1
[0091] This comparative example is modified as follows based on Example 1:
[0092] No diethylene glycol dimethyl ether was added to the cutting fluid.
[0093] Comparative Example 2
[0094] This comparative example is modified as follows based on Example 1:
[0095] No triethanolamine was added to the cutting fluid.
[0096] Comparative Example 3
[0097] This comparative example is modified as follows based on Example 1:
[0098] No sulfolane was added to the cutting fluid.
[0099] Comparative Example 4
[0100] This comparative example is modified as follows based on Example 1:
[0101] Calculated by mass fraction, the cutting fluid consists of the following chemical components: 3 parts of diethylene glycol dimethyl ether, 1 part of triethanolamine, 0.5 parts of sodium chloride, 2 parts of sulfolane, 1 part of surfactant, 0.5 parts of aluminum corrosion inhibitor, 0.15 parts of extreme pressure agent, and 91.85 parts of deionized water.
[0102] Comparative Example 5
[0103] This comparative example is modified as follows based on Example 1:
[0104] The cutting fluid is composed of the following chemical components by mass fraction: 3 parts of diethylene glycol dimethyl ether, 1 part of triethanolamine, 0.5 parts of sodium chloride, 2 parts of sulfolane, 1 part of surfactant, 0.5 parts of aluminum corrosion inhibitor, 0.15 parts of extreme pressure agent, and 91.85 parts of dolomite-based nanofluid.
[0105] Comparative Example 6
[0106] This comparative example is modified as follows based on Example 1:
[0107] The cutting fluid is composed of the following chemical components by mass fraction: 3 parts of diethylene glycol dimethyl ether, 1 part of triethanolamine, 0.5 parts of sodium chloride, 2 parts of sulfolane, 1 part of surfactant, 0.5 parts of aluminum corrosion inhibitor, 0.15 parts of extreme pressure agent, and the balance is zirconium oxide-based nanofluid.
[0108] Comparative Example 7
[0109] This comparative example is modified as follows based on Example 1:
[0110] Measured by mass fraction, the cutting fluid consists of the following chemical components: 3 parts of diethylene glycol dimethyl ether, 1 part of triethanolamine, 0.5 parts of sodium chloride, 2 parts of sulfolane, 1 part of surfactant, 0.5 parts of aluminum corrosion inhibitor, 0.15 parts of extreme pressure agent, 0.46 parts of dolomite, 0.184 parts of zirconium oxide, 0.092 parts of quaternized sodium alginate, and 91.11 parts of deionized water.
[0111] Comparative Example 8
[0112] This comparative example is modified as follows based on Example 1:
[0113] The dolomite / zirconia-based nanofluid is composed of dolomite (CAS No.: 69227-00-5), zirconium oxide and deionized water, wherein the dolomite accounts for 0.5% of the total mass of the dolomite / zirconia-based nanofluid, and the zirconium oxide accounts for 0.2% of the total mass of the dolomite / zirconia-based nanofluid.
[0114] Comparative Example 9
[0115] This comparative example is modified as follows based on Example 1:
[0116] The step S31 in the method for preparing the cutting fluid is not performed.
[0117] Comparative Example 10
[0118] This comparative example is modified as follows based on Example 1:
[0119] In step S31, the mixed solution is subjected to a single microwave treatment.
[0120] Comparative Example 11
[0121] This comparative example is modified as follows based on Example 1:
[0122] In step S31, the mixed solution is subjected to a single ultrasonic combined treatment.
[0123] Comparative Example 12
[0124] This comparative example is modified as follows based on Example 1:
[0125] The aluminum corrosion inhibitor is a siloxane ketone corrosion inhibitor (MILLION siloxane ketone aluminum corrosion inhibitor AC-3S).
[0126] The cutting fluids obtained in Examples 1 to 5 and Comparative Examples 1 to 12 were subjected to performance tests, and the results are shown in Table 1.
[0127] According to GB / T6144-2010, the original solution storage stability, aluminum corrosion and foam tendency of aluminum alloy cutting fluid were determined.
[0128] According to JB / T9189-2016, the anti-rust property of the solution was determined.
[0129] According to the self-built method and referring to JB / T7453, the hard water resistance of the solution was determined: a 1000 mg / L hard water solution dilution with a concentration of 5% (mass fraction) was prepared, and the solution was allowed to stand for 24 hours at room temperature to test the hard water resistance. Preparation of hard water: 0.555 g of anhydrous calcium chloride and 1.015 g of magnesium chloride with crystal water were placed in a 1000 mL volumetric flask, and dissolved and diluted to the mark with distilled water to obtain a 1000 mg / L hard water solution.
[0130] The corrosion resistance of aluminum alloy was tested according to the GB / T6144-2010 test method. At 55℃±2℃, 5% (mass fraction) aqueous solution was prepared respectively, and the polished 2A12 aluminum alloy specimen was placed in the cutting fluid dilution solution for complete immersion for 24 hours, and then the specimen was taken out for inspection.
[0131] Table 1 Performance of cutting fluids obtained in Examples 1 to 5 and Comparative Examples 1 to 9
[0132]
[0133]
[0134] As shown in Table 1, the cutting fluid provided by the present application has a foam height of ≤3 cm, a rust resistance of grade 0, no precipitate in a 1000 mg / L hard water solution dilution, a corrosiveness of grade A, and a friction coefficient of <0.5. Comparative Examples 1 to 10 lack important components or steps, resulting in varying degrees of performance degradation.
[0135] The cutting fluid of Example 1 was used in an aluminum cutting processing factory, and the on-site processing conditions are shown in Table 2.
[0136] Table 2 Application of cutting fluid in Example 1
[0137] Knives Polycrystalline Diamond <![CDATA[Processing speed, r·min -1 > 7000~7500 Material ADC12 aluminum alloy Cutting depth / mm 0.25~0.30
[0138] It can be seen from Table 2 that the machining accuracy of aluminum alloy parts meets the requirements and there is no corrosion on the aluminum alloy surface.
[0139] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0140] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0141] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An environmentally friendly fully synthetic water-based aluminum alloy cutting fluid, characterized in that: The cutting fluid is composed of the following chemical components in parts by mass: 2.0 to 5.0 parts of diethylene glycol dimethyl ether, 0.5 to 1.5 parts of triethanolamine, 0.1 to 1.0 parts of sodium chloride, 1.0 to 3.0 parts of sulfolane, 0.5 to 1.5 parts of surfactant, 0.1 to 1.0 parts of aluminum corrosion inhibitor, 0.05 to 0.3 parts of extreme pressure agent, and 85 to 96 parts of dolomite / zirconia-based nanofluid; Wherein, the dolomite / zirconia-based nanofluid consists of dolomite, zirconium oxide, quaternized sodium alginate and deionized water.
2. The cutting fluid according to claim 1, characterized in that: The dolomite is 0.3-0.7% of the total mass of the dolomite / zirconia-based nanofluid; and / or, The zirconium oxide is 0.1-0.3% of the total mass of the dolomite / zirconia-based nanofluid; and / or, The mass of the quaternized sodium alginate is 0.05-0.15% of the total mass of the dolomite / zirconia-based nanofluid.
3. The cutting fluid according to claim 2, characterized in that: The aluminum corrosion inhibitor consists of a siloxane ketone corrosion inhibitor and a phosphate ester corrosion inhibitor, and the mass ratio of the siloxane ketone corrosion inhibitor to the phosphate ester corrosion inhibitor is (1-3):
1.
4. The cutting fluid according to claim 1, characterized in that: The extreme pressure agent is composed of dialkyl dithiocarbamate molybdenum and sodium metaborate, and the mass ratio of the dialkyl dithiocarbamate molybdenum to the sodium metaborate is (0.5-1.5):
1.
5. The cutting fluid according to claim 1, characterized in that: The surfactant is composed of an oleic acid amide-based nonionic surfactant and an alkyl imidazoline borate, and the ratio of the oleic acid amide-based nonionic surfactant to the alkyl imidazoline borate is (3-8):
1.
6. The cutting fluid according to claim 1, characterized in that: The dolomite has a particle size of 20 to 50 nm; and / or, The particle size of the zirconium oxide is 1 to 10 nm.
7. A method for preparing a cutting fluid according to any one of claims 1 to 6, characterized in that: The method comprises: A dolomite / zirconia-based nanofluid is obtained; Under stirring, adding diethylene glycol dimethyl ether, triethanolamine, sodium chloride, sulfolane, a surfactant, an aluminum corrosion inhibitor and an extreme pressure agent to the dolomite / zirconia-based nanofluid in sequence to obtain a mixed solution; The mixed liquid is subjected to microwave-ultrasound combined treatment to obtain the cutting fluid.
8. The method according to claim 7, characterized in that The process parameters of the microwave-ultrasonic combined treatment include: microwave power of 50-150W, ultrasonic power of 100-200W, and combined treatment time of 60-180s.
9. The method according to claim 7, characterized in that: The preparation method of the dolomite / zirconia-based nanofluid comprises: ball-milling dolomite and zirconium oxide to obtain a mixture; The mixture, quaternized sodium alginate and deionized water are mixed, and then subjected to homogenization and dispersion treatment to obtain the dolomite / zirconia-based nanofluid.
10. The method according to claim 9, characterized in that The homogenization and dispersion process includes the following parameters: a homogenization pressure of 100 to 140 MPa and a homogenization time of 10 to 30 minutes.